How Digital Maturity Drives Operational Efficiency: A Multi Sector Analysis - Syahruddin, Syahruddin (Amkop Management Accounting Review (AMAR), 2024)
This study investigates the extent to which digital maturity enhances operational efficiency across multiple industrial sectors in 2024. As organizations continue to adopt digital technologies, understanding the measurable impact on operational performance becomes critically important. A quantitative cross-sectional survey was conducted involving 200 organizations from five sectors: manufacturing, finance, retail, healthcare, and utilities. The data were analyzed using Structural Equation Modeling (SEM) to test construct reliability, validity, and the hypothesized relationship between digital maturity and operational efficiency. The results demonstrate a significant positive relationship between digital maturity and operational efficiency (β = 0.62, p < 0.001), with the model explaining 39% of performance variance. Sectoral comparison reveals notable differences, where finance and healthcare exhibit higher digital maturity compared to manufacturing and retail, indicating uneven digital transformation progress across industries. Organizations are encouraged to accelerate digital capability development—particularly in sectors facing legacy and infrastructure challenges—to enhance efficiency and remain competitive. The findings further highlight the need for human capital readiness and supportive digital culture to maximize technological investments. This study offers a multi-sector perspective on how digital maturity drives operational outcomes, providing actionable insights for both academia and industry stakeholders in advancing digital transformation strategies.